Mac OS X Lion in depth - Ness, Robyn (Que, 2011)
Beyond the Basics...Beneath the Surface...In Depth Mac OS X Lion in Depth Do more with Mac OS X Lion-in less time! Mac OS X Lion In Depth is a comprehensive guide to Mac OS X Lion, grounded in real-world advice and experience. The author, Robyn Ness, is a long-time Mac user and provides practical instruction on how to get up and running with Lion, and then move on to more advanced features and options. • Streamline your workflow with Mission Control and Spaces • Organize your apps with Launchpad • Get the most from Lion's multitouch gestures • Set up your desktop and apps to give you a clean start or resume where you left off • Purchase and download apps from the Mac App Store and run full-screen apps • Manage contacts, calendars, and email • Set up user accounts and parental controls • Configure wired and wireless networking • Chat, video chat, and screen-share with Lion's iChat and FaceTime • Use the Safari web browser for reading lists, bookmarks, and RSS • Share files with nearby Lion users with AirDrop • Run Windows and Windows apps on your Mac • Activate Universal Access and accessibility features • Recover files through Versions and Time Machine • Use Lion's built-in disk recovery options Mac OS X Lion In Depth is for any experienced Mac user seeking to deepen their understanding and master the features of the new version of Mac OS X. All In Depth books offer Comprehensive coverage with detailed solutions Troubleshooting help for tough problems you can't fix on your own Outstanding authors recognized worldwide for their expertise and teaching style Learning, reference, problem-solving... the only Mac OS X Lion book you need!